2005
DOI: 10.1507/endocrj.52.471
|View full text |Cite
|
Sign up to set email alerts
|

A C/T Polymorphism in the 5' Untranslated Region of the CD40 Gene Is Associated with Later Onset of Graves' Disease in Japanese

Abstract: Abstract. Graves' disease (GD) is an autoimmune disorder with genetic predisposition. CD40, which stimulates lymphocyte proliferation and differentiation, is an important immunomodulator and is expressed in the thyroid follicular cells as well as antigen-presenting cells. A single nucleotide polymorphism (SNP) at position -1 of the Kozak sequence of the CD40 gene has been reported to be associated with the development of GD. The aim of the present study was to investigate whether CD40 gene polymorphism confers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 31 publications
1
32
1
Order By: Relevance
“…Previously, we 12 and others [15][16][17][18] have shown that a SNP, in the Kozak sequence of the CD40 gene, is associated , showing significant CD20 expression only in lymph node, spleen and thymus. All other tissues did not show significant CD20 expression ruling out blood contamination.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previously, we 12 and others [15][16][17][18] have shown that a SNP, in the Kozak sequence of the CD40 gene, is associated , showing significant CD20 expression only in lymph node, spleen and thymus. All other tissues did not show significant CD20 expression ruling out blood contamination.…”
Section: Discussionmentioning
confidence: 82%
“…Subsequent case-control association studies demonstrated an association of the CC genotype with GD. 12 With the exception of a sole report, 14 the association between the CC genotype and GD has now been replicated in several studies, performed in different populations, including Caucasians, 12,15 Koreans 16 and Japanese 17,18 (an additional report purporting a lack of association between the C allele and GD 19 was found, upon re-analysis, to show an association between the CC genotype and GD 20 ). Moreover, a meta-analysis of all studies showed a highly significant association between the CC genotype and GD.…”
Section: Introductionmentioning
confidence: 97%
“…The genetic susceptibility of these diseases is thought to be polygenic. It has been reported that major histocompatibility complex (MHC) gene [3,4], cytotoxic T lymphocyte antigen-4 (CTLA-4) gene [4][5][6], thyrotropin receptor (TSHR) gene [7], PTPN22 gene [8], CD40 gene [9,10], interferon-γ (IFN-γ) gene [11], tumor necrosis factor-α (TNF-α) gene [12,13] and interleukin-13 (IL-13) gene [14] polymorphisms are associated with GD and their interactions may influence disease phenotype and severity [3]. However, their contribution to susceptibility to GO awaits confirmation.…”
mentioning
confidence: 99%
“…SNPs in non-coding regions can regulate the binding activity of transcriptional factors by altering the structure of some transcriptional domain binding sites (Jeng et al, 2008;Shibata et al, 2009;Ucisik-Akkaya et al, 2010). Using statistical analysis, Mukai et al (2005) found that SNP in the 5'-untranslated region of the CD40 gene had some influence on its expression, and Ordovás et al (2008) found the g.763G>C SNP in the 5'-untranslated region of the bovine FASN gene affects its promoter activity. Moreover, Sun et al (2010) found that the rs11868112 SNP locus on the 26-kb gene upstream of the RPTOR gene altered the RAR and POU2F1 transcription factor binding sites, which led to a decrease in gene expression (as determined by RT-PCR and ChIP methods) in response to climatic adaptations.…”
Section: Discussionmentioning
confidence: 99%